A Systematic Review of Biological Mechanisms of Fatigue in Chronic Illness. Issue 4 (July 2018) - Matura, Lea Ann; Malone, Susan; Jaime-Lara, Rosario; Riegel, Barbara
Fatigue, a commonly reported symptom, is defined as an overwhelming, debilitating, and sustained sense of exhaustion that decreases the ability to function and carry out daily activities. To date, cancer researchers have been in the forefront in investigating the possible biological mechanisms of fatigue, identifying inflammation, dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, and activation of the autonomic nervous system. The purpose of this systematic review is to describe fatigue and what is known about the biological mechanisms described in cancer in five chronic, noninfectious illnesses: heart failure, multiple sclerosis, chronic kidney disease, rheumatoid arthritis, and chronic obstructive pulmonary disease. We searched PubMed and EMBASE using fatigue as a major Medical subject headings (MeSH) heading with each individual disease added as a search term followed by each biological mechanism. We included only primary research articles published in English between 1996 and 2016 describing studies conducted in adult humans. We identified 26 relevant articles. While there is some evidence that the biological mechanisms causing fatigue in cancer are also associated with fatigue in other chronic illnesses, more research is needed to explore inflammation, the HPA axis, and the autonomic nervous system, and other mechanisms in relation to fatigue in a variety of chronic illnesses.